1987
DOI: 10.1136/gut.28.suppl.25
|View full text |Cite
|
Sign up to set email alerts
|

Jejunal bypass stimulation of pancreatic growth and cholecystokinin secretion in rats: importance of luminal nutrients.

Abstract: SUMMARYThe effect of jejunal bypass on pancreatic growth and plasma cholecystokinin (CCK) was investigated in rats. Rats underwent bypass of jejunum or sham operation. Rats with jejunal bypass were further divided into three groups; one group received a continuous infusion of a partially hydrolysed liquid diet (Vital) into the bypassed jejunum; a second group received the nutrient solution mixed with trypsin and infused into the bypassed jejunum; the third bypass group did not receive infusion of nutrient or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…Similar to the observations of Spannagel and Green (23), and Levan et al (24), we found that peptone could stimulate CCK secretion in rats with diversion of bile pancreatic juice. Peptides appear to mediate the effect of peptone because mixed amino acids were ineffective to evoke pancreatic secretion or plasma CCK release.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar to the observations of Spannagel and Green (23), and Levan et al (24), we found that peptone could stimulate CCK secretion in rats with diversion of bile pancreatic juice. Peptides appear to mediate the effect of peptone because mixed amino acids were ineffective to evoke pancreatic secretion or plasma CCK release.…”
Section: Discussionsupporting
confidence: 81%
“…Peptides appear to mediate the effect of peptone because mixed amino acids were ineffective to evoke pancreatic secretion or plasma CCK release. It has been proposed that luminal nutrients may be necessary to maintain normal CCK synthetic activity and that the release of CCK occurs spontaneously in the absence of the suppressive effects of pancreatic proteases (24). Our studies clearly demonstrate that peptone in the duodenum acts by stimulating the luminal secretion of CCK-RP and this in turn stimulates the release of CCK.…”
Section: Discussionsupporting
confidence: 57%
“…In the rat it has been well demonstrated that diversion of pancreatico-biliary juice from the duodenum, or inhibition of duodenal pancreatic enzyme activity with trypsin inhibitors, causes a prompt increase in pancreatic exocrine secretion (17). It has recently been confirmed that CCK is stimulated both by pancreatic diversion and trypsin inhibitor ingestion, and CCK appears to mediate the negative feedback regulation of pancreatic secretion (18,19). In other species such as the dog it has been extremely difficult to demonstrate feedback regulation, and in humans the existence of similar negative feedback regulation has been debated (20-22).…”
Section: Discussionmentioning
confidence: 87%
“…Since these experiments were done using CCK-8, the role of CCK-58 remains unknown [50,51]. However, similar findings were ob-served during pancreatic juice diversion [52], which releases endogenous CCK [53,54] that is presumably the natural form. CCK-mediated pancreatic secretion is potently inhibited by PYY only when the AP is intact, thus requiring a vagal-vagal pathway [47].…”
Section: Discussionmentioning
confidence: 50%